2021
DOI: 10.1038/s41598-021-99114-1
|View full text |Cite
|
Sign up to set email alerts
|

A transfer learning framework based on motor imagery rehabilitation for stroke

Abstract: Deep learning networks have been successfully applied to transfer functions so that the models can be adapted from the source domain to different target domains. This study uses multiple convolutional neural networks to decode the electroencephalogram (EEG) of stroke patients to design effective motor imagery (MI) brain-computer interface (BCI) system. This study has introduced ‘fine-tune’ to transfer model parameters and reduced training time. The performance of the proposed framework is evaluated by the abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 29 publications
(18 reference statements)
1
10
0
Order By: Relevance
“…They evaluated intra-and inter-subject transfer learning calibrations using data from seven stroke patients and found that their scheme benefitted low-precision sessions the most. In [56], Xu et al studied transfer learning with a combination of healthy and stroke data, collected from eleven healthy and five stroke patients. They used EEGNet for transfer learning based on fine-tuning and achieved an average accuracy of 66.36%.…”
Section: Transfer Learning In Stroke Patientsmentioning
confidence: 99%
“…They evaluated intra-and inter-subject transfer learning calibrations using data from seven stroke patients and found that their scheme benefitted low-precision sessions the most. In [56], Xu et al studied transfer learning with a combination of healthy and stroke data, collected from eleven healthy and five stroke patients. They used EEGNet for transfer learning based on fine-tuning and achieved an average accuracy of 66.36%.…”
Section: Transfer Learning In Stroke Patientsmentioning
confidence: 99%
“…Some studies have investigated the use of motor imagery electroencephalogram (MI-EEG) signal classification for developing prosthetic limbs that can be controlled by the user's intention to move their limbs [3,4]. Other studies have focused on developing MI-EEG classification models for stroke rehabilitation, where the models can be used to evaluate the effectiveness of rehabilitation programs and track patients' progress [5][6][7]. Given the potential contributions of MI-EEG for the development of motor imagery BCI applications, there appears to be a need for methodologies that can present solutions for performing well across diverse individuals and conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The speller systems are the most popular and widespread type of BCI applications that can help patients to write their thoughts just by focusing on the virtual keyboard through brain signals without using their hands [ [4] , [5] , [6] ]. These applications are suitable for patients who are unable to use their muscles normally, such as amyotrophic lateral sclerosis (ALS), spinal cord injury (SCI), Duchenne muscular dystrophy (DMD), and stroke [ 7 , 8 ]. Electroencephalogram (EEG) is often used for measuring non-invasive brain signals in BCI applications such as steady-state visually evoked potential (SSVEP) [ 9 , 10 ], P300-based event-related potential (ERP) [ 11 ], sensorimotor rhythm (SMR) [ 12 ], and slow cortical potential (SCP) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%